Antecedent infections in Guillain‐Barré syndrome in endemic areas of arbovirus transmission: A multinational case‐control study. Issue 4 (30th September 2021) - Leonhard, Sonja E.; Tan, Cheng Yin; van der Eijk, Annemiek A.; Reisin, Ricardo R.; Franken, Suzanne C.; Huizinga, Ruth; Arends, Samuel; Batstra, Manou R.; Bezerra Jeronimo, Selma M.; Drenthen, Judith; de Koning, Laura; Leon Cejas, Luciana; et al.
Abstract: Half of the world's population is at risk of arthropod‐borne virus (arbovirus) infections. Several arbovirus infections have been associated with Guillain‐Barré syndrome (GBS). We investigated whether arboviruses are driving GBS beyond epidemic phases of transmission and studied the antibody response to glycolipids. The protocol of the International Guillain‐Barré syndrome Outcome Study (IGOS), an observational prospective cohort study, was adapted to a case‐control design. Serum samples were tested for a recent infection with Zika virus (ZIKV), dengue virus (DENV), chikungunya (CHIKV) virus, hepatitis E virus, Epstein‐Barr virus (EBV), cytomegalovirus (CMV), Campylobacter jejuni, and Mycoplasma pneumoniae, and for antibodies to glycolipids. Forty‐nine patients were included from Brazil (63%), Argentina (14%), and Malaysia (22%). Evidence of a recent infection was found in 27/49 (55%) patients: C jejuni (n = 15, 31%), M pneumoniae (n = 5, 10%), CHIKV (n = 2, 4%), EBV (n = 1, 2%), C jejuni and M pneumoniae (n = 2, 4%), CMV and DENV (n = 1, 2%), and C jejuni and DENV (n = 1, 2%). In 22 patients, 35 paired controls were collected. Odds ratio for recent infections did not significantly differ between cases and controls. No typical anti‐ganglioside antibody binding was associated with recent arbovirus infection. We conclude that arbovirus infections occur in GBS patients outside of epidemic viral transmission, although not significantly more than in controls. Broad infection and anti‐ganglioside antibody serology are important to establish the most likely pathogenic trigger in GBS patients. Larger studies are necessary to determine the association between arboviruses and GBS.